The Validity and Engagement of the OSTRC‐H2 Questionnaire as a Surveillance Tool to Detect Health Problems in a High‐Performance Australian Youth Diving Cohort: An Observational Study - Alison S. Fitch; Jocelyn Mara; Michael Hetherington; Kate Mahony; Michael K. Drew; Gordon Waddington (Health Science Reports)
ABSTRACT Background and Aims The Oslo Sports Trauma Research Centre (OSTRC) questionnaire on health problems was developed to monitor self‐reported health problems and their severity in junior and elite sporting populations but has yet to be validated in a youth diving cohort. This study aimed to assess the validity and degree of athlete engagement with the OSTRC‐H2 questionnaire among youth Australian divers over 10 weeks and also report on their health problems via medical attention records. Methods Thirty‐seven youth Australian divers completed the OSTRC‐H2 every Sunday for 10 consecutive weeks and also continued to report all medical attention health problems to their health professional during this period. Results Engagement showed that the mean response rate was 72.3%, with a high variation among athletes (SD = 27.0%, range = 10.0%–100.0%). When accounting for missing reports, agreement with medical attention records indicated 93.8% for illness (±10.4), 82.4% for injury (±24.9), and 74.4% for training status (±25.1). Notably, the OSTRC‐H2 recorded more illnesses (n = 7, 16 reports) than medical attention records (n = 4, 5 reports). During the 10‐week surveillance period, 97 medical attention records were created, documenting 25 injuries and 4 illnesses. Conclusion The OSTRC‐H2 demonstrated a moderate to high response rate and good agreement (excluding missing reports) as a surveillance tool. It effectively identifies health problems in this cohort, particularly illness, and may assist to minimize severity and reduce time‐loss health problems, positively impacting training and competition performance for youth Australian high‐performance divers.